2012
DOI: 10.1007/978-3-642-30870-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Hard Instances of Algorithms and Proof Systems

Abstract: Abstract. Assuming that the class Taut of tautologies of propositional logic has no almost optimal algorithm, we show that every algorithm A deciding Taut has a polynomial time computable sequence witnessing that A is not almost optimal. The result extends to every Π p t -complete problem with t ≥ 1; however, we show that assuming the Measure Hypothesis there is a problem which has no almost optimal algorithm but has an algorithm without hard sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Then f ∈ L PV and we claim that there is a nonstandard n ∈ M such that f M {0, 1} n is a mad pseudo proof system in K (F n PV ). We can assume that ∀yFml( f (y)) holds in N and hence in M. So to get the madness property (7) it suffices to get M |= ψ(n) for the formula ψ(x) defined in (8). Now, for g ∈ L PV let B g, f : N → N map m ∈ N to For g ∈ L PV and standard > 0 let ϕ g, f, (x) be the formula…”
Section: Proof Of Theorem 13mentioning
confidence: 99%
See 2 more Smart Citations
“…Then f ∈ L PV and we claim that there is a nonstandard n ∈ M such that f M {0, 1} n is a mad pseudo proof system in K (F n PV ). We can assume that ∀yFml( f (y)) holds in N and hence in M. So to get the madness property (7) it suffices to get M |= ψ(n) for the formula ψ(x) defined in (8). Now, for g ∈ L PV let B g, f : N → N map m ∈ N to For g ∈ L PV and standard > 0 let ϕ g, f, (x) be the formula…”
Section: Proof Of Theorem 13mentioning
confidence: 99%
“…(b)⇒(c) and (d)⇒(a) are trivial. To prove (c)⇒(d) we proceed as in [, Proposition 3.2] using a padding function: a polynomial time computable function pad that maps a formula F and a string y{0,1} to a formula pad (F,y) of length at least |F|+|y| that has the same satisfying assignments as F , and such that there are two polynomial time functions mapping any input of the form pad (F,y) to F and y , respectively. Let double-struckA be a sat ‐solver and assume (c).…”
Section: Hard Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen, Flum and Müller [CFM11] generalize this result from optimal acceptors to optimal algorithms. Graph (non)isomorphism and optimality up to permutations of vertices.…”
Section: Introductionmentioning
confidence: 77%
“…While it is easy to see that Messner's proof goes for randomized acceptors as well, it does not apply to computations with advice (where optimal proof systems exist [CK07], but no optimal acceptors are known), heuristic computations (where optimal acceptors do exist [HINS11], but no optimal proof systems are known), or the restricted notion of optimality used in this paper. Recently, it was shown that the existence of optimal acceptors is equivalent for all co -NP-complete languages [CFM11].…”
Section: Introductionmentioning
confidence: 99%